A new species of the genus Osornolobus Forster & Platnick from the maulino forests of Chile (Araneae, Orsolobidae) - Grismado, Cristian J.; Pizarro-Araya, Jaime (Zootaxa, 2023)
A faunistic survey in the Maule region in central-southern Chile resulted in the discovery and description of a new species of the spider genus Osornolobus: O. violetaparra n. sp., based on males collected using pitfall traps in the province of Talca. This is the northernmost record of the genus in Chile, previously known from Ñuble to Magallanes.